Presentation of Ocular Syphilis in a HIV-Positive Patient with False-Negative Serologic Screening - Mahsaw N. Motlagh; Cameron G. Javid (Case Reports in Infectious Diseases)
Purpose. The ocular sequelae of syphilis are devastating and may cause blindness. The ambiguous nature of its ocular manifestations makes syphilis difficult to detect. Though uncommon, the rise of syphilis in the United States requires a renewed understanding of its ophthalmic presentation to prevent devastating outcomes. We present this case to raise awareness for the increasing prevalence of ocular syphilis and appropriate serologic testing. Observations. We describe a 65-year-old HIV-positive male with worsening retinitis, uveitis, and rapid visual loss. Initial lab results showed a nonreactive rapid plasma reagin (RPR) for syphilis. However, subsequent Treponema pallidum antibody testing was positive 48 hours after initial false-negative serologic screening. The patient had a rapid and successful recovery following treatment with penicillin. Conclusions and Importance. The incidence of syphilis is on the rise once again, and patients living with HIV are at increased risk. Ocular syphilis should be considered in susceptible populations in the clinical setting of retinitis, uveitis, and worsening visual loss with unknown cause. In addition, retesting for syphilis will decrease the prevalence of false-negative results, especially in patients with high clinical suspicion.